The pact : a love story. - Picoult, Jodi, 1966- (New York : HarperPerennial Modern Classics, 2009)
A teenage suicide pact between a pregnant girl and her boyfriend, both children of wealthy New England families. He shoots her, but fails to shoot himself and is charged with murder. At the trial he explains what made them do it.
Includes P.S. : Insights, interviews & more.
Originally published: New York : HarperCollins, 1998.
Accelerated Reader AR
Keywords: Teenagers -- Death -- Fiction; Teenagers -- Suicidal behavior -- Fiction; Psychological fiction